2020
DOI: 10.7554/elife.59902
|View full text |Cite
|
Sign up to set email alerts
|

Group size and composition influence collective movement in a highly social terrestrial bird

Abstract: A challenge of group-living is to maintain cohesion while navigating through heterogeneous landscapes. Larger groups benefit from information pooling, translating to greater ‘collective intelligence’, but face increased coordination challenges. If these facets interact, we should observe a non-linear relationship between group size and collective movement. We deployed high-resolution GPS tags to vulturine guineafowl from 21 distinct social groups and used continuous-time movement models to characterize group m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 54 publications
3
49
1
Order By: Relevance
“…In addition to intensi ed competition for resource with increased densities, social interactions such as increased aggression may affect bird movement and spacing behavior. Papageorgiou and Farine (2020) have found that social group size reduced home ranges of vulturine guineafowl (Acryllium vulturinum) when group size exceeded a threshold [77]. We found that home range size and hourly movement distance decreased with increasing AWPE relative abundance.…”
Section: Discussionsupporting
confidence: 50%
“…In addition to intensi ed competition for resource with increased densities, social interactions such as increased aggression may affect bird movement and spacing behavior. Papageorgiou and Farine (2020) have found that social group size reduced home ranges of vulturine guineafowl (Acryllium vulturinum) when group size exceeded a threshold [77]. We found that home range size and hourly movement distance decreased with increasing AWPE relative abundance.…”
Section: Discussionsupporting
confidence: 50%
“…Study species: We studied two habituated social groups of individually colour-banded vulturine guineafowl living in the savannah and dry-woodland habitat surrounding Mpala Research Centre (0°17ʹN, 37°52ʹE) in Laikipia County, Kenya. These birds live in stable social groups [31,32] and frequently engage in aggressive and submissive interactions with group members that result in steep dominance hierarchies [33].…”
Section: Empirical Datamentioning
confidence: 99%
“…However, it may also induce challenges if it limits the options available to individuals that live in cohesive groups relative to individuals that live in more open societies. For example a small patch might provide sufficient resources for an individual or a small group, but not for a larger group [26]. Addressing this gap requires a better understanding of how group behaviours change over the spectrum of conditions that each group is likely to experience.…”
Section: Introductionmentioning
confidence: 99%